The Code of the State of Georgia. Adopted December 15th, 1895. Vol. 3 Page 147 (1896) § 511 - (:unkn) unknown (General Publisher, 1892)
Prohibited throwing rocks or other missiles at, towards, or into a passenger train on a railroad. Also prohiited shooting any gun, pistol, or firearms of any kind at, towards, or into any such car. Violators guilty of a misdemeanor.
--
Keywords: DISCHARGE